2015
DOI: 10.3390/su7078292
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Model to Explain How Corporate Social Responsibility Affects Corporate Financial Performance

Abstract: Abstract:The effect of corporate social responsibility (CSR) on financial performance has important implications for enterprises, communities, and countries, and the significance of this issue cannot be ignored. Therefore, this paper proposes an integrated model to explain the influence of CSR on financial performance with intellectual capital as a mediator and industry type as a moderator. Empirical results indicate that intellectual capital mediates the relationship between CSR and financial performance, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
152
0
13

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(175 citation statements)
references
References 87 publications
10
152
0
13
Order By: Relevance
“…The positive effect of CSR on financial performance is consistent with many studies conducted in Western, Asian, and other countries (e.g., [4,[16][17][18]43]). Additionally, in the context of Zambia, Choongo et al [20] established that SMEs are motivated to engage in CSR for financial benefits.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The positive effect of CSR on financial performance is consistent with many studies conducted in Western, Asian, and other countries (e.g., [4,[16][17][18]43]). Additionally, in the context of Zambia, Choongo et al [20] established that SMEs are motivated to engage in CSR for financial benefits.…”
Section: Discussionsupporting
confidence: 75%
“…There has been an increase in CSR studies (e.g., [16][17][18][19][20]). Despite the increase in research on CSR, there is still no generally agreed definition of CSR [21], as a result there is an ambiguous use of the terminology [22].…”
Section: Csr In Smesmentioning
confidence: 99%
“…For this reason, this study covers firms belonging to diverse industries and controls for this factor. Lin et al [69] indicate that industry type moderates the direct influence of CSR on financial performance.…”
Section: Industry (Activity Sector)mentioning
confidence: 99%
“…Restaurant company attitudes can play vital roles in the success of innovation adoption and sustainable relevant practices [23]. While prior research has proven that innovation in services serves as the driving ingredient for sustainable restaurant operations [24], few studies have examined these innovations from a systematic perspective on sustainability. Despite the before-mentioned studies have shown that the key roles of sustainable service innovation in the service industry, restaurant sustainable service innovation has been neglected in relevant research.…”
Section: Introductionmentioning
confidence: 99%